IMPLEMENTATION OF THE PROJECT-BASED LEARNING (PJBL) MODEL AS AN ATTEMPT TO IMPROVE THE THIRD-GRADE STUDENTS’ CRITICAL THINKING SKILLS AT SDN 004 RANTAU KOPAR - Nofiarida (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2023)
Critical thinking is a skill in thinking by using the process of analyzing and evaluating a problem to produce the right decisions in solving the problem. PJBL is a learning model that applies problems as the first stage in acquiring new knowledge based on the experience of concrete life activities. Project Based Learning is a learning model that provides opportunities for teachers to manage learning in class by involving work projects. This paper describes the implementation of the project-based learning (PjBL) model in improving students' critical thinking skills. The research used was Classroom Action Research (CAR) using the Kemmis and Mc. Taggart research design models. The cycle consisted of planning, action, observation, and reflection. The research was conducted at SDN 004 Rantau Kopar. The research subjects involved 22 students of class III (Three). Teacher and students activities increased from cycle I to cycle II with an average teacher activity score of 69.92. Meanwhile, student activity average scores were 67.89, both of which increased in each cycle. Conversely, the results of critical thinking skills indicate a significant increase to a very good category, with an average value of 53, 70, and 85 for each cycle. After conducting the improvement phase in cycle II, the student test results reveal a significant increase to a very good category.